Parvovirus enteritis in two dogs - Abdul Rahman, Sheikh Omar; Cheng, B. Y.; Ibrahim, A. L.; Chooi, Kum Fai (Malaysian Society of Applied Biology, 1985)
Two cases of haemorrhagic enteritis in the dog with clinical manifestation and pathological changes consistent with parvovirus enteritis are reported. Electron microscopic examination of faeces from both dogs revealed the presence of particles resembling parvovirus.